1999
DOI: 10.1016/s1071-3581(99)90024-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic criteria for detection of postinfarction ischemia by quantitative analysis of stepwise dobutamine radionuclide ventriculography

Abstract: Application of appropriate criteria and stepwise quantitative analysis of RNV during dobutamine infusion may increase accuracy in the detection of early postinfarction ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…25 Accuracy and reproducibility of phase analysis and LVEF measurement by ERNA in our laboratory has been previously evaluated and published elsewhere. 22 An example of baseline, LDD and CRT follow-up parametric phase imaging evaluation of ERNA in a dobutamine-responder patient is shown in Figure 1.…”
Section: Radionuclide Studymentioning
confidence: 99%
See 2 more Smart Citations
“…25 Accuracy and reproducibility of phase analysis and LVEF measurement by ERNA in our laboratory has been previously evaluated and published elsewhere. 22 An example of baseline, LDD and CRT follow-up parametric phase imaging evaluation of ERNA in a dobutamine-responder patient is shown in Figure 1.…”
Section: Radionuclide Studymentioning
confidence: 99%
“…This value has been previously determined by ROC analysis to be the best prognostic cut-off point. 13,25 Clinical end-points during the follow-up period were the major adverse cardiac events (MACE) defined as (1) cardiac death, (2) index re-hospitalization for worsening heart failure or (3) heart transplantation. …”
Section: Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients early after AMI, it has been examined by echocardiography [1,2,3,4], radionuclide ventriculography [5, 6] and cardiac magnetic resonance imaging (DCMR) [7,8,9]. Dosing of dobutamine ranged from 5 to 40 µg*kg –1 *min –1 .…”
Section: Introductionmentioning
confidence: 99%
“…Dosing of dobutamine ranged from 5 to 40 µg*kg –1 *min –1 . A low contractile response of dysfunctional myocardium to dobutamine was attributed to post-infarction ischemia [5] and myocardial necrosis [4], whereas a positive contractile response was interpreted as myocardial stunning [6, 8]. The only study comparing different doses of dobutamine in AMI-patients observed different responses of an echocardiographic myocardial performance index and a wall motion score index at low- and high-dose dobutamine [3].…”
Section: Introductionmentioning
confidence: 99%